Changes in the inflammatory markers with supplementation of channa striatus extract in post lower segment caesarean section - Shafii, Noorazliyana (International Medical Journal, 2017)
Objective: Channa striatus or Haruan was found to have beneficial effect for wound healing and anti-intlammatory due to its' amino acids and fatty acids content. The obj ective of this study was to determine the effect of C. striatus supplementation on intlammatory markers which are high sensitive C-reactive protein (hsCRP), total white cell counts (TWCC) and platelet counts in post Lower Segment Caesarean Section (LSCS) patients. Desig11: This was a randomized; double blinded, placebo-controlled study among post LSCS women conducted in Hospital Univer siti Sains Malaysia from March 2010 to December 2012. Material and Methods: A Total of 33 patients from Cstriatus and 27 patients from placebo group were included in this study. Participants in the treatment group consumed 500 mg of freeze dried c..~triatus extract daily while the participants in pl acebo group consumed 500 mg of placebo daily for 3 days. Venous bloods for hsCRP, TWCC and platelet counts were taken from each par ticipant postoperati vely at day I and day 3. Resulls: Within C. striatus group, there wer e significant redu ction in hsCRP (P < 0.001) and TWCC (P < 0.001), with significant increase in platelet count (P < 0.001) from day I to day 3. Similar pattern of changes were observed within control group. Between group compar ison at day 3 post oper atively indicates no significant difference in hsCRP (P = 0.275), TWCC (P = 0.983) and platelet count (P = 0.206) between the two groups. Co11clusion: In conclusion, there is no significant difference in the infl ammatory markers durin g wound healing in post LSCS women.